MicroRNA-5195-3p alleviates high glucose‑induced injury in human ARPE-19 cells by targeting GMFB. - Jingjing Liu; Yongsheng Hou; Lili Lin; Nannan Yu; Yanyan Zhang (PLoS ONE, 2021)
Hyperglycemia is generally considered to be an important cause of diabetic retinopathy (DR). The aim of the present study was to investigate the role of miR-5195-3p in high glucose (HG)-induced human retinal pigment epithelial ARPE-19 cell injury. Here, we first found that the expression level of miR-5195-3p was significantly downregulated in HG-stimulated ARPE-19 cells using reverse transcription quantitative PCR. Overexpression of miR-5195-3p attenuated the impaired cell viability, increased apoptosis and pro-inflammatory cytokines secretion in ARPE-19 cells under HG condition using CCK-8 assay, flow cytometry and ELISA assay, respectively. Luciferase reporter assay showed that miR-5195-3p could specifically bind to the 3'UTR of glia maturation factor-β (GMFB). GMFB overexpression reversed, while knockdown enhanced the protective effects of miR-5195-3p overexpression against HG-induced ARPE-19 cell injury. In summary, miR-5195-3p targeting GMFB might be a potential therapeutic target for DR.